Quality of vaccination session in the primary healthcare setting at Saudi Arabia - Khloud Khalid Alsadi,; Abdulaziz Abed Qabel Alqurashi,; Mohammed Ahmed Almanjoomi,; Khaled Awad Almalki,; Naif Mabruk Abdullah Alqurashi,; Maryam Ahmed Mohammad Alkhalifa,; Abeer Zaki Ahmed Alabbas,; Afeefa Mohammad Hussan Aldakheel,; Taghreed Muslin Almehyawi,; Taghreed Khalid Alshahrani,; Naif Mohammed Alharthi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Vaccination is a major health promotive weapon. Hence, proper vaccination session management practicesis the core for successful immunization, reduction of vaccines wastage rate and its associated cost which drain country resources.The aim to assess the Quality of vaccination session in the primary healthcare setting at Saudi Arabia Research design: A descriptive cross- sectional research design was utilized. Setting: This study was conducted in vaccination clinics at the following settings ; King Faisal Residential City Clinic ( Jeddah Housing ); King Khalid Residential City Clinic ( Taif Housing ); Al-Madena Al-Monawarh Housing Clinic; Khozam Clinic; Bahra Clinic; Um Assalam Clinic; Sharia Clinic; Yanbu Clinic; Jeezan Clinic affiliated to the Ministry of Health of Saudia Arabia. Subjects: The study comprised all of the healthcare provides(350) who worked in the immunization clinics of the family health centers that were previously chosen. Tools of the study: Tool I: general vaccination family center questionnaire; Tool II: quality of Vaccination Session Management Practices. Data collection :The researchers observed the vaccination session using tool (II) and gathered information about the management practices of the vaccination session for each vaccine administered to every child during the vaccination session (8.30 am:12.30 pm). Over the course of one month (January–February 2024), data was gathered from the chosen family health centers twice a week. Results: this study clarified that the Multi Dose vaccination Policy (MDVVP), Vaccine Vial Monitor (VVM) policy, and monthly report for vaccination usage rate were all in written form at all of the family health centers under study. None of them, meanwhile, provide a monthly report on the rate and trends of vaccine waste. Furthermore, 90.8% of the immunization sessions under study had moderate levels of vaccine management techniques, whereas 2.2% had high levels, Low preparation practices were found in all of the immunization sessions under study; however, moderate (74.0%) to high (21.7%) conducting practices were noted. However, there are high concluding procedures in every immunization session. Conclusion:Most of the analyzed immunization sessions had mediocre to poor results. overall management procedures for vaccination sessions, based on the current study's findings. Specifically, the preparatory practices for every session were low, and most of the conduction practices were moderate.